Biomechanical Evaluation of a Modified Internal Brace Construct for the Treatment of Ulnar Collateral Ligament Injuries. Issue 10 (1st October 2019) - Urch, Ekaterina; Limpisvasti, Orr; ElAttrache, Neal S.; Itami, Yasuo; McGarry, Michelle H.; Photopoulos, Christos D.; Lee, Thay Q.
Background: Ulnar collateral ligament (UCL) repair augmented with the "internal brace" construct for the management of acute UCL injuries has recently garnered increasing interest from the sports medicine community. One concern with this technique is excessive bone loss at the sublime tubercle, should revision UCL reconstruction be required. In an effort to preserve the bony architecture of the sublime tubercle, an alternative internal brace construct is proposed and biomechanically compared with the gold standard UCL reconstruction. Hypothesis: The internal brace repair construct will restore valgus laxity and rotation to its native state and demonstrate comparable load-to-failure characteristics with the 3-strand reconstruction technique. Study Design: Controlled laboratory study. Methods: For this study, 8 matched pairs of fresh-frozen cadaveric elbows were randomized to undergo either UCL reconstruction with the 3-ply docking technique or UCL repair with a novel internal brace construct focused on augmenting the posterior band of the anterior bundle of the ligament (modified repair-IB technique). Valgus laxity and rotation measurements were quantified through use of a MicroScribe 3DLX digitizer at various flexion angles of the native ligament, transected ligament, and repaired or reconstructed ligament. Laxity testing was performed from maximum extension to 120° of flexion. Each specimen was then loaded to failure, and the method of failure was recorded. Results: Valgus laxity was restored to the intact state at all degrees of elbow flexion with the modified repair-IB technique, and rotation was restored to the intact state at both full extension and 30°. In the reconstruction group, valgus laxity was not restored to the intact state at either full extension or 30° of flexion ( P < .001 and P = .004, respectively). Laxity was restored at 60° of flexion, but the elbow was overconstrained at 90° and 120° of flexion ( P = .027 and P = .003, respectively). In load-to-failure testing, the reconstruction group demonstrated significantly greater yield torque (19.1 vs 9.0 N·m; P < .005), yield angle (10.2° vs 5.4°; P = .007), and ultimate torque (23.9 vs 17.6 N·m; P = .039). Conclusion: UCL repair with posterior band internal bracing was able to restore valgus laxity and rotation to the native state. The construct exhibited lower load-to-failure characteristics when compared with the reconstruction technique. Clinical Relevance: In selected patients with acute, avulsion-type UCL injuries, ligament repair with posterior band internal bracing is a viable alternative surgical option that, by preserving bone at the sublime tubercle, may decrease the complexity of future revision procedures.